IMPROVING CIVICS LEARNING OUTCOMES THROUGH AUDIOVISUAL-ASSISTED CONTEXTUAL TEACHING AND LEARNING (CTL) - Salwa Anazainiah Rustam (CV Grasta Glory, 2026)
Civics Education (PPKN) learning in elementary schools often faces challenges such as low student motivation and limited use of engaging instructional media, which can negatively affect learning outcomes. Therefore, this study aims to examine the effect of the Audiovisual-Assisted Contextual Teaching and Learning (CTL) model on students’ PPKN learning outcomes. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, acting, observing, and reflecting stages. The subjects of the study were 17 fifth-grade students at SD Negeri 37 Lubuklinggau, comprising 9 male and 8 female students. Data were collected through observations, tests, interviews, and documentation, and analyzed descriptively. The results indicated a significant improvement in students’ learning outcomes. In Cycle I, the average pre-test score was 61.76%, increasing to 67.06% in the post-test. In Cycle II, the pre-test average score improved to 77.65%, while the post-test score reached 87.06%. In conclusion, the Audiovisual-Assisted CTL model effectively improves Civics Education learning outcomes. It is recommended that teachers apply this model regularly and utilize varied audiovisual media to enhance student engagement and understanding.